A study on the market performance analysis for TA Enterprise Berhad during economic downturns / Muhamad Fahmi Mansor - Mansor, Muhamad Fahmi (Faculty of Business and Management, 2009)
The purpose of this study is to provide a detailed financial performance evaluation focus on market measure or market performance of TA Enterprise Berhad. This paper uses key financial ratios which is market measures of the financial performance of this company. The calculated ratios will be analyzed and used for the financial performance evaluation. The research only include data which has been derived from TA Enterprise Berhad income statements, balance sheet, and statements of cash flows under their financial statements in their annual reports from the year 2005 to year 2009. By assessing their ledgers, this research could test the feasibility or the appropriateness of the published financial statement. Additionally, other methods which are time consuming are expelled from this research. These other methods may play an important role in the financial performance evaluation as well.